The Effectiveness of Cognitive Behavior Play Therapy (CBT) in Improving Attention in Children with Attention Deficit Disorder (ADD) - Pratiwi, Ayu; Faradillah, Dita; Perdana, Daffa Affan; Fatimatussa’diah, Ervina; Yulia, Eva (JOYCED: Journal of Early Childhood Education, 2026)
Purpose - Attention Deficit Disorder (ADD) is a neurodevelopmental disorder marked by persistent difficulties in sustaining attention, which negatively impact children’s academic, social, and emotional functioning. One promising non-pharmacological intervention is Cognitive Behavioral Play Therapy (CBPT), an approach that combines cognitive-behavioral strategies with developmentally appropriate play activities to improve attention and self-regulation. Design/methods/approach - This study employed a literature review by searching PubMed, ScienceDirect, Sage Journal, and Google Scholar using relevant keywords. The inclusion criteria were articles in Indonesian or English, published between 2017–2025, with quasi-experimental or experimental designs, and focusing on CBPT interventions in children with ADD/ADHD. Study selection followed the PICOS framework and PRISMA analysis. Findings - From 26 identified articles, only 2 met the criteria. Findings showed that CBPT effectively reduced inattentive symptoms (Khatoon, A., Iqbal, N., & Masroor, 2020) and significantly improved attention and planning skills in children with ADHD (Hir et al., 2023). Research implications/limitations - Interventions were delivered in 10–20 sessions using structured play methods such as role play, modeling, storytelling, and puppet play. Originality/value - In conclusion, CBPT has proven effective in enhancing attention and executive function in children with ADD, supporting its application as an evidence-based non-pharmacological intervention in clinical and educational settings for children, families, and professionals.